Post-marketing drug safety surveillance of enfortumab vedotin: an observational pharmacovigilance study based on a real-world database - Yu, Mingming; Zhou, Lijun; Cao, Mengda; Ji, Chunmei; Zheng, Yuanyi (Frontiers in Immunology, 2024)
Background: Enfortumab vedotin (EV) is an antibody-drug conjugate (ADC), which is approved by FDA for patients with locally advanced or metastatic urothelial carcinoma (UC). This study present a comprehensive pharmacovigilance analysis of the post-marketing safety profile of EV in real-world based on the US Food and Drug Administration Adverse Event Reporting System (FAERS). Methods: Adverse event(AE) reports regarding EV during January 2020 to December 2023 were obtained from the FAERS database. The standardized MedDRA query (SMQ) narrow search AEs on the preferred term (PT) level were used. Disproportionality analysis was performed to identify the AE signals for EV with reporting odds ratio (ROR), proportional reporting ratio (PRR), and multi-item gamma poisson shrinker (MGPS), bayesian confidence propagation neural network (BCPNN). Results: Totally 2216 reports regarding EV were included in the present study. SMQ analysis result indicated that a stronger strength signal was found in severe cutaneous adverse reactions, retroperitoneal fibrosis and peripheral neuropathy. Totally 116 significant disproportionality PTs refer to 14 system organ class(SOC) were retained by disproportionality analysis, with 49 PTs were not list in EV the drug label. Frequently reported EV-related AEs included rash, peripheral neuropathy, decreased appetite, alopecia, pruritus,etc.The time to onset of majority EV-related AEs were reported within 30 days(66.05%), with only 0.73% events after 1 year.The disproportionality analysis highlights that dermatologic toxicity and peripheral neuropathy were the major AEs induced by EV. The potential AEs without listing in drug label main foucs on gastrointestinal, hepatic, pulmonary events. Further research is need to confirm and explore the EV-related AEs in clinical .